Evaluating the effects of urban development on the ecological carrying capacity of Isfahan city based on the system dynamics approach - Zahra Dehghan Manshadi; Parastoo Parivar (علوم محیطی, 2023)
Introduction: The management of social-ecological systems such as cities is extremely complicated due to the interdependence of subsystems, the cause-and-effect relationships that exist between them, and the impacts on sustainability. The necessity of ecological capacity and the ability of cities to sustain their potential to provide goods and services to both current and future generations cannot be overstated. Understanding how arid ecosystems adapt to disturbances is critical for the sustainable management of such areas, given the global extent of this type of ecosystem and its fragility, both structurally and functionally. The purpose of this study is to assess the impacts of urban growth on the carrying capacity of Isfahan, which is located on Iran's central plateau. In this regard, simulation models can be an effective tool in providing scientific decisions in dealing with complex and unknown social and ecological systems.Material and methods: In this study, system dynamics modeling was used to determine the cause-and-effect relationships between variables affecting Isfahan's carrying capacity. In order to examine the landscape structure, DIVISION, SPLIT, and IJI metrics have been used to show connectivity, and ED, SHDI, and AI metrics have been used to determine the heterogeneity of the landscape of Isfahan City. After problem articulation, the model boundary was defined in the initial step of the modeling process by developing the subsystem diagram. After the population, environment, landscape, and carrying capacity subsystems were evaluated, a cause-and-effect diagram was made. The flow diagram and scenario were also made to evaluate the state of Isfahan's carrying capacity. In order to validate the model, the historical trend and simulation of two variables of urban population and the number of industries have been compared using the coefficient of determination.Results and discussion: The pressure factors on the urban carrying capacity were detected and analyzed by assessing key variables in the system, such as water sustainability (WSI) and air quality, as well as changes in the landscape structure of Isfahan using landscape metrics. The research findings indicate that approximately 90% of the urban water demand is dedicated to the domestic sector; therefore, the first scenario is related to the management of water consumption in this sector and its influence on the Water Supply–Demand Index. This scenario showed that if domestic water demand is not controlled, the result of this index will reach nearly 0.7 by 2040, indicating greater vulnerability to the region's water resources. The second scenario is related to the city's increasing trend of construction and the number of industries, the impact of which has been shown on the carrying capacity.Conclusion: The current study's findings, based on two enlarged scenarios, demonstrated that water demand, changes in the structure of the urban landscape, and the growth of industries all have a major impact on Isfahan's carrying capacity. Therefore, by controlling and managing water consumption in the domestic sector, limiting industrial growth, preventing the destruction of gardens, enhancing urban green and open areas, and limiting the increase of impervious urban surfaces, Isfahan's carrying capacity will improve.